Poor Bone Quality in Patients With Amyotrophic Lateral Sclerosis - Caplliure-Llopis, Jordi; Escrivá, Dolores; Benlloch, María; de la Rubia Ortí, José Enrique; Estrela, José María; Barrios, Carlos (Frontiers in Neurology, 2020)
Objective: Musculoskeletal deterioration in Amyotrophic lateral sclerosis (ALS) is associated with an increase in bone fractures. The purpose of this study was to evaluate the influence of sex, clinical type, on bone quality in patients with ALS compared to healthy controls. The impact on bone health of the clinical status and some metabolic parameters was also analyzed. Methods: A series of 33 voluntary patients with ALS, and 66 healthy individuals matched in sex and age underwent assessment of bone mass quality using quantitative ultrasound (QUS) of the calcaneus. Bone mineral density (BMD) was estimated using standard equations. Clinical baseline measures in ALS patients included ALSFRS-R score, Barthel index for activities of daily living, pulmonary function, and muscular strength. Laboratory tests included serum calcium, Vitamin D, alkaline phosphatase), T4 and TSH. Results: All bone parameters evaluated were statistically significant lower in ALS patients than in healthy controls. ALS females showed significantly lower bone parameters than healthy females. According to the estimated BMD, there were 25 ALS patients (75.8%) and 36 (54.5%) healthy individuals showing an osteoporotic profile. There was no correlation between any of the clinical parameters analyzed and the bone measurements. Vitamin D and TSH levels correlated with all the bone parameters. Conclusions: This study confirms that ALS patients, particularly females, exhibited deteriorated bone health as compared to healthy individuals. These bone changes were independent of ALS subtype and clinical status. Bone health in ALS patients seems to be related to certain metabolic parameters such as Vitamin D and TSH..